Factors Affecting the Outcomes of First in vitro Fertilization and Embryo Transfer: A Retrospective Investigation - Muhaidat N; Karam AM; Nabhan MS; Dabbah T; Odeh B; Eid M; Almahallawi NJ; Alshrouf MA (Dove Medical Press, 2023)
Nadia Muhaidat,1 Abdulrahman M Karam,2 Mohammed Saad Nabhan,1 Tala Dabbah,2 Bilal Odeh,2 Mira Eid,2 Nadia Jamal Almahallawi,3 Mohammad Ali Alshrouf2 1Department of Obstetrics & Gynaecology, School of Medicine, The University of Jordan, Amman, 11942, Jordan; 2The School of Medicine, The University of Jordan, Amman, 11942, Jordan; 3Department of Family Medicine, School of Medicine, The University of Jordan, Amman, 11942, JordanCorrespondence: Nadia Muhaidat, Department of Obstetrics & Gynaecology, School of Medicine, The University of Jordan, Amman, 11942, Jordan, Tel +962798385775, Email Nadiadat@hotmail.comBackground: The outcome of embryo transfer (ET) is multifactorial. A variety of patient-related, procedural-related, and operator-related factors are known to play a role. This study aims to evaluate the outcomes of ET and determine the factors that affect the outcome.Methods: The study involved a retrospective design involving 300 first in vitro fertilization and embryo transfer (IVF-ET) cycles between 2011 and 2021. The outcome included 155 unsuccessful cycles and 145 successful IVF-ET leading to pregnancy. The outcomes were examined for different variables, including age, weight, height, body mass index, cause of infertility, number of embryos fertilized during the cycle, day of ET, whether the embryo was frozen, presence of blood or mucus during the procedure, the use of a stylet, tenaculum, uterine sound/dilator, and catheter type. Logistic regression was used to analyze factors affecting the outcomes of ET.Results: The mean age was 27.84 ± 3.77 years. Patients who had blood during the procedure (32.9% vs 17.2%, p = 0.002), mucus (31% vs 20.7%, p = 0.049), or used the tenaculum (16.8% vs 6.9%, p = 0.012) were more likely to have unsuccessful IVF-ET. Logistic regression to adjust for related factors revealed that the presence of blood (AOR = 2.21, 95% CI 1.04 to 4.66, p = 0.038) during the ET had a higher likelihood of an unsuccessful outcome.Conclusion: This study showed that the presence of blood during the ET cycle influenced clinical pregnancy. This highlights the importance of performing the procedure under atraumatic conditions.Level of Evidence: Level III; retrospective comparative study.Plain Language Summary: Infertility is considered an important public health problem in terms of high expenses, treatment complications, and failure. Addressing the factors that impact embryo transfer outcomes may help in guiding counseling and management. Therefore, the aim of this study was to evaluate the results of IVF-ET and assess several patient-related and procedural-related factors that impact those results. It included retrospectively 300 cycles from 2011 to 2021. The presence of blood after embryo transfer was shown to be the major predictor of an unsuccessful cycle. Moreover, although the usage of additional instruments was not significantly associated with a higher risk of failed embryo transfer cycles, the operators should use these instruments with caution in order to avoid any trauma that might result in bleeding.Keywords: IVF, assisted reproductive technique, infertility, pregnancy, predictive factors